The ‘Green Revolution’ dwarfing genes play a role in disease resistance in Triticum aestivum and Hordeum vulgare - Saville, R. J. (Oxford University Press, 2012)
The Green Revolution dwarfing genes, Rht-B1b and Rht-D1b, encode mutant forms of DELLA proteins and are present in most modern wheat varieties. DELLA proteins have been implicated in the response to biotic stress in the model plant, Arabidopsis thaliana. Using defined wheat Rht near-isogenic lines and barley Sln1 gain of function (GoF) and loss of function (LoF) lines, the role of DELLA in response to biotic stress was investigated in pathosystems representing contrasting trophic styles (biotrophic, hemibiotrophic, and necrotrophic). GoF mutant alleles in wheat and barley confer a resistance trade-off with increased susceptibility to biotrophic pathogens and increased resistance to necrotrophic pathogens whilst the converse was conferred by a LoF mutant allele. The polyploid nature of the wheat genome buffered the effect of single Rht GoF mutations relative to barley (diploid), particularly in respect of increased susceptibility to biotrophic pathogens. A role for DELLA in controlling cell death responses is proposed. Similar to Arabidopsis, a resistance trade-off to pathogens with contrasting pathogenic lifestyles has been identified in monocotyledonous cereal species. Appreciation of the pleiotropic role of DELLA in biotic stress responses in cereals has implications for plant breeding.